Formação de professores: um olhar inter-transdisciplinar no curso de pedagogia - Sousa, Juliane Gomes de (Universidade Federal do Tocantins, 2018)
This dissertation focuses on teacher formation in the light references of interdisciplinarity and transdisciplinarity. With this, the main objective is to analyze the curriculum and pedagogical actions developed in the teachers initial formation of the Pedagogy course at the University Campus of Tocantinópolis, with reference to the theoretical-epistemological foundations of interdisciplinarity and transdisciplinarity. The methodological path covered is supported by the exploratory case study, supported by the qualitative approach. In the data collection, a subjective questionnaire was used as instrument, with 43 students, and observation techniques, documentary analysis, and interview with 11 teachers of said educational reality. From the systematization of the data, which is in close articulation with the studied theorists, it is verified that the teacher formation in contemporaneity demands the resignification of the models that have historically characterized them. Regarding the context investigated, it was detected that although there are pedagogical actions that seek an extension in the traditional ways of teaching and learning, these are located sporadically and in a punctual way that few teachers do, standing out, as a priority practice, The methodological attitudes that are rooted in the characteristics of the traditional approach: expositive classes, isolationism in the teaching work, deficiency in teaching and research connection. Regarding the curriculum, the time lag is established, established as static since its structuring period. In addition, it is verified that the organization that prevails in the curricular matrix is based on the verticalization and compartmentalization of knowledge areas. The analysis can contribute to the creation of reflections in the formative scenario of the course, which from the investigative process carried out reveals the need to rethink the pedagogical actions that are consolidated, as well as the curriculum that is materialized in its context, in view of the Expansion of the formative dimensions of the pedagogue. The reflections carried out also make it possible to visualize a fragility in the exclusively transmissive and linear model of teaching, which has contributed to the realization of empty practices of meaning for students and teachers. Thus, it is pointed out that the formation based on the inter-transdisciplinary approach is characterized by a vision of dialogue, openness, integration, appreciation of diversity, sensitive listening, partnerships and cooperation. These elements are considered as potential for triggering transformative practices and attitudes in the educational scenario.